2022
DOI: 10.48550/arxiv.2201.02167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of selection -- a tale of cluster mass measurement bias induced by correlation and projection

Yuanyuan Zhang,
James Annis

Abstract: Cosmology analyses using galaxy clusters by the Dark Energy Survey have recently uncovered an issue of previously unknown selection effect affecting weak lensing mass estimates. In this letter, we use the Illustris-TNG simulation to demonstrate that selecting on galaxy counts induces a selection effect because of projection and correlation between different observables. We compute the weak-lensing-like projected mass estimations of dark matter halos, and examine their projected subhalo counts. In the 2-D proje… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Clusters are not selected by their host halo mass, they are rather selected by their stellar or gas observables. As first pointed out by Nord et al (2008) and later shown by others (e.g., Farahi et al 2018b;Zhang & Annis 2022), a non-zero covariance between observables can induce a non-trivial biases in mass-observable relation if not accounted for properly. As we will show, this bias is not a constant factor, rather it is a function of mass and radial distance.…”
Section: Cluster Mass Calibrationmentioning
confidence: 89%
See 1 more Smart Citation
“…Clusters are not selected by their host halo mass, they are rather selected by their stellar or gas observables. As first pointed out by Nord et al (2008) and later shown by others (e.g., Farahi et al 2018b;Zhang & Annis 2022), a non-zero covariance between observables can induce a non-trivial biases in mass-observable relation if not accounted for properly. As we will show, this bias is not a constant factor, rather it is a function of mass and radial distance.…”
Section: Cluster Mass Calibrationmentioning
confidence: 89%
“…Consequently, the covariance between the baryon and dark matter density profiles not only provides new insights on the interactions between dark matter, gas, and stars at different scales, but is also an important model ingredient when performing multi-wavelength cluster mass calibration or a cross-correlation analysis. For instance, when clusters are selected on their observables, other than halo mass, this covariance matrix can induce additive bias in the expected properties of halos, such as the weak-lensing signal (Zhang & Annis 2022). In this paper, we quantify the impact of this covariance on the expected cumulative mass profile for a optically-selected cluster sample.…”
Section: Introductionmentioning
confidence: 99%
“…Sartoris et al 2016). Projection effects can introduce large selection biases in cosmological cluster studies based on weak-lensing mass estimates (Sunayama et al 2020;Abbott et al 2020;Zhang & Annis 2022). Optical observations have a wealth of information, which is currently not fully utilized by weak-lensing studies, instead relying on assumptions of sphericity for large enough samples of clusters.…”
Section: Discussionmentioning
confidence: 99%